2018
DOI: 10.1111/obr.12786
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lifestyle energy expenditure in the management of obesity and health: from biology to built environment

Abstract: Increasing lifestyle energy expenditure has long been advocated in the prevention and treatment of obesity, as embodied in the ancient prescription of Hippocrates (the 'father of modern medicine') that people with obesity should eat less and exercise more. However, the long-term outcome of exercise alone or in combination with dieting in obesity management is poor. To understand the reasons underlying these failures and to develop novel strategies that target lifestyle energy expenditure in both prevention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…From our data, we evaluated the association of circulating free-fatty acid (FFA) and glucose concentrations with δRQ 1 h after a 75-g OGTT. 42 We observed that the change in FFA and glucose concentrations after 1 h of glucose ingestion was inversely associated with δRQ ( Figure 3A,B). For FFA, this finding suggests that greater suppression of adipose tissue lipolysis decreases circulating and tissue fatty acid availability, thus boosting glucose oxidation.…”
Section: Intake Levelmentioning
confidence: 77%
See 1 more Smart Citation
“…From our data, we evaluated the association of circulating free-fatty acid (FFA) and glucose concentrations with δRQ 1 h after a 75-g OGTT. 42 We observed that the change in FFA and glucose concentrations after 1 h of glucose ingestion was inversely associated with δRQ ( Figure 3A,B). For FFA, this finding suggests that greater suppression of adipose tissue lipolysis decreases circulating and tissue fatty acid availability, thus boosting glucose oxidation.…”
Section: Intake Levelmentioning
confidence: 77%
“…RQ is sensitive to energy balance, where positive energy balance favors high RQ. 41 An analysis of our data 42 shows a positive association between δRQ and energy balance, the latter calculated as energy intake 54,55 Thus, a high-carbohydrate diet (i.e., high FQ) results in an elevated carbohydrate oxidation with concomitant suppression of lipid oxidation (i.e., high 24-h RQ). When fat intake increases (i.e., low FQ), a progressive increase in lipid oxidation is noted along with lowered carbohydrate oxidation (i.e., low 24-h RQ).…”
Section: Intake Levelmentioning
confidence: 85%
“…However, investigating energy flux and pairing of energy intake to energy demand in human participants is complicated by the large interindividual variability of total and physical activity EE (8,9). Also, increased physical activity produces multiple systemic and tissue-specific adaptations independent of increases in EE (10,11), further complicated by sex-specific differences in physical activity level and physiological adaptation (12,13). As such, new approaches are necessary to more specifically assess the independent impact of changes in EE on energy balance and protection from weight gain.…”
Section: Study Importancementioning
confidence: 99%
“…The observations, analytical approaches and research outcomes of his classic studies have impacted, and continue to‐date to impact, several avenues of research and concept development in the field of human obesity and chronic metabolic disease. This latter realization turned out to be an ideal theme for celebrating the 10th edition of the Fribourg Obesity Research Conference (FORC)—which, since its first edition in 2001, has been a platform to present and discuss some of the rapidly advancing scientific findings pertaining to obesity and health from perspectives that cut across integrative physiology, nutrition, and public health 5–13 . This current supplement to Obesity Reviews is thus dedicated to the legacy of Ancel Keys and its impact on current concepts in obesity research as embodied in the eight review papers that were presented at the 10th FORC, and which are put into perspective below.…”
Section: Introductionmentioning
confidence: 99%